Exposure–Response Relationship between VWF/FVIII Activity and Spontaneous Bleeding Events Following Recombinant VWF Prophylaxis in Severe VWD - Leebeek, Frank W.G.; Castaman, Giancarlo; Marier, Jean François; Özen, Gülden; Bhattacharya, Indranil; Zhang, Jingmei; Wang, Scarlett; Wang, Yi (TH Open, 2024)
Background Recombinant von Willebrand factor (rVWF, vonicog alfa, Takeda Pharmaceuticals USA) is indicated in adults diagnosed with von Willebrand disease (VWD). In this study, the exposure–response (ER) relationship between VWF activity (VWF:RCo) or factor VIII activity (FVIII:C) and spontaneous bleeding events (BEs) was evaluated in adults with severe VWD receiving rVWF prophylaxis for up to 1 year.Methods This secondary analysis included 23 patients receiving rVWF prophylaxis in the open-label, phase 3 prophylaxis trial (NCT02973087). Population pharmacokinetic (PK) and PK/pharmacodynamic (PD) models were used to characterize VWF activity and endogenous FVIII:C, and PK/PD simulations were linked to spontaneous BEs to develop an ER model.Results None of the five patients with VWD types 1 or 2A/B experienced spontaneous BEs. Five of 18 patients with VWD type 3 experienced ≥1 spontaneous BEs. An ER relationship was observed whereby higher VWF:RCo levels were associated with a numerically lower spontaneous BE risk (p < 0.10). This relationship was independent of patients' pretrial VWF treatment. A statistically significant ER relationship was observed after accounting for relevant data (average ± standard error exposure estimate for VWF:RCo over 24 hours prior to the spontaneous BE: −0.043 ± 0.021, p = 0.041). The model-generated hazard ratio for a 10 IU/dL increment in the average exposure of VWF:RCo 24 hours before a spontaneous BE was 0.651 (95% confidence interval: 0.431–0.982).Conclusions This ER analysis suggests a causal association between VWF:RCo and spontaneous BEs, with an increase of VWF:RCo exposure leading to a decrease in spontaneous BE risk.
Keywords: bleeding; prophylaxis; recombinant VWF; vonicog alfa; von Willebrand disease; factor VIII